Language learning motivation: a com arative study between english and mandarin language learners / Siti Faridah Kamaruddin, Ting Hie Ling and Aisyah Nazamud-Din - Kamaruddin, Siti Faridah; Ling, Ting Hie; Nazamud-Din, Aisyah (Universiti Teknologi MARA, 2020)
The current study was conducted with the objectives of investigating the level of language learning motivation among Malaysian university students in comparison between two preferred languages, which are English as a second language (ESL) and Mandarin as a foreign language (MFL) and at the same time, identifying the motivational orientations among the participants of this study. This study adapted quantitative methodology to measure the level of language learning motivation as well as the motivational orientation among respondents. The participants consisted of 330 students from three higher learning institutions where English and Mandarin are offered as language subjects. In general, students who participated in this study displayed a high level of language learning motivation for both languages. However, the findings showed that the students were highly motivated toward learning English as compared to Mandarin. In the perspective of motivational orientation, students are more extrinsically inclined to learn English and Mandarin. Students are more extrinsically motivated to learn English because they think both English and Mandarin will someday be useful in getting a job. The study supports the claim that different languages learned might trigger different emotional responses from learners. Hence, the results from this study also assisted in the discussion of the commandments on how language educators can motivate their learners.